The Effectiveness of Canopy Trees to Reduce Rainfall Acidity in the Industrial Area at Medan - Basuki, Tyas Mutiara (Forum Geografi, 2000)
The term of acid rain is referred to the mean rainfall with a pH less than 5,65. The element of Sox and Nox are the major sources of aid rain. These two elements are oxidized into SO4 and NO3 respectively in the air. Sulfate and Nitrate are water soluble and the primary sources of hydrogen ions in acid precipitation. Rain passing through a tree canopy may lose or gain mineral elements trough some combination of natural process of absorption and leaching. By this process, the canopy may reduce rainfall acidity and negatif effects of the acid rain which will enter into the soil. Due to characteristic differences among tree canopies, a study to evaluate effectiveness of the trees in reducing rainfall acidity was done. In this study, rainfall and troughfall were collected every single rain and the pH measure by portable pH-meter. Based on data collection during 3 months in Medan Industrial Estate, it found that the mean pH of rainfall was 5,15. The highest pH of throughfall was found from Gnetum gnemon, that was 5,70; following by Mimusops elengi, Filicium decipiens, Acacia mangium, and the lowest was Nephelium lappacum. G. Gnemon was able to reduce 11% of rainfall acidity, but N. Lappacum caused 13% increasing rainfall acidity. In this study, the main source of rainfall acidity was hidrogen from sulfate acid (54%), following by chloride acid (30%), and nitrate acid (16%).